Palladium catalysed hydroesterification and aminocarbonylation of substituted alkenes and alkynes - Du Plessis, Maretha (University of the Free State, 2018)
Since the aim of this study was to investigate the influence of the electronic environment around the double bond of alkenes on the reactivity and regioselectivity of the methoxycarbonylation reaction for developing new methodology towards the synthesis of isoflavonoids, several aryl substituted alkenes were subjected to methoxycarbonylation utilizing the Pd(OAc)2/Al(OTf)3/PPh3 catalyst system in MeOH under the optimum conditions of 35 bar of CO pressure and 95 °C. In order to be able to compare current results with literature values, 1-octene, 2-octene and styrene, were the first substrates to be methoxycarbonylated and gave anticipated high conversions (100%, 83% and 91%, respectively) to the expected linear (l) and branched (b) methyl esters, methyl nonanoate and methyl 2-methylnonanoate as well as methyl 3-phenylpropanoate and methyl 2- phenylpropanoate, respectively in a l:b ratio of ca. 3:1. A set of trans-β-methylstyrene analogues, i.e. trans-β-methylstyrene, trans-p-methoxy-β-methylstyrene and trans-omethoxy- β-methylstyrene as well as a set of allylbenzene analogues, i.e. allylbenzene, pmethoxyallylbenzene, p-trifluoromethylallylbenzene, o-methoxyallylbenzene and otrifluoromethanesulfonyloxyallylbenzene were subjected to the methoxycarbonylation reaction conditions and the products obtained in high conversions (88-96%) except for the alkenes with methoxy substituents in the para-position, i.e. p-methoxy-β-methylstyrene and p-methoxyallylbenzene (49% and 66%, respectively). During these investigations isomerization of the double bond in the β-methylstyrenes to the terminal position, forming allylbenzene analogues proved to be a feasible side-reaction, so the same products, i.e. linear (l), branched (b) and benzylic (bn) carboxylated products were formed from the β- methylstyrenes and corresponding allylbenzenes. During the investigation it was also found that a p-methoxy substituent on the β-methylstyrene or allylbenzene resulted in a decrease in reaction rate, while an o-methoxy substituent increases the reaction rate substantially in comparison to the p-methoxy analogues. Ortho-substituents (methoxy or triflate group) also resulted in a drastic increase in the formation of the linear products for both the β- methylstyrene and allylbenzene substrates, i.e. 3:2:1 vs. 10:4:1 and 8:2:1 vs. 15:5:1 vs. 5:1:0, respectively. It was also determined that a more electron-rich aromatic ring has an enhancing effect on the formation of the benzylic products as was determined by the methoxycarbonylation of 1,3-diphenylpropene, which gave methyl 2,4-diphenylbutanoate in 64% yield and 95% regioselectivity. Sterically more demanding disubstituted and trisubstituted double bonds, like in α-methylstyrene and 2-methyl-1-phenylprop-1-ene, were also subjected to the methoxycarbonylation reaction and resulted in the formation of methyl 3- phenylbutanoate in 63% and methyl 3-methyl-4-phenylbutanonate in 26% yield, respectively, albeit after extended reaction periods (4-6 h). Since the availability of CO and thus the CO concentration in solution should have a significant influence on the rate of the reactions unless CO is not involved in the rate limiting step of the process, the effect of mass transfer limitations on the reaction rate of the substrates mentioned above were also studied and it was found that an 8-18% increase in reaction rates were observed for conditions of proper mass transfer for styrene, allylbenzene, and p- and omethoxyallylbenzenes where isomerization of the double bond is insignificant. Since hydroesterification under microwave radiation conditions has not been reported to date, the effect, if any, of microwave radiation vs. thermal heating conditions were also investigated. Owing to the pressure limit (12 bar) of the glass reaction vessel in the microwave reactor all reactions were executed at 12 bar in order to allow direct comparison of the results and a definite increase in reaction rate (99% conversion after only 10 min. vs. 99% after 30 min. at 35 bar) was observed for the microwave hydroesterification reactions of 1- octene and styrene. Although a general increase in reaction rate was not found for the allylbenzene substrate, a ca. 15% increase in yield was observed for p-methoxyallylbenzene (20% vs. 37%), o-methoxyallylbenzene (73% vs. 89%) and β-methylstyrene (66% vs. 88%) as substrates when the microwave reactions were compared to those performed under conventional heating under the same pressure. When the nucleophile in the carbonylation reactions was changed from oxygen (methanol) to nitrogen (aniline) and the ligand to BINAP in the same catalyst system, the first aminocarbonylation reaction was observed. Reaction of the o- and p-methoxy substituted allylbenzenes with aniline, anisidine and 4-chloroaniline resulted in the successful formation of the linear and branched amides (anilides) in 87-97% yield. Extending the methodology to trans-β-methylstyrene and α-methylstyrene with aniline, however, gave the amides in only 18% and 16% yield, respectively. When the aminocarbonylation of allylbenzene was investigated with strongly deactivated anilines (2,4-dichloro- and 4-nitroaniline), primary amines (butylamine and benzylamine) and amides (acetamide) no product formation could be detected, so it was suspected that the reaction may be dependent on the pKa of the amine, with pKa-values below 3 being too acidic and pKa-values above 9 basic enough to be deactivated by complexation to the Lewis acid [Al(OTf)3] in the catalyst system. Although the successful hydroamidation (25% conversion) of 4-chlorobenzylamine (pKa = 9.17) gave some credence to this hypothesis, this aspect of the investigation still needs more attention in a follow-up investigation. Subsequently, attention was turned towards the original aim of this project, i.e. methoxycarbonylation of stilbene analogues. Unsubstituted stilbene, 4-methoxystilbene and 2-methoxystilbene, however, gave poor results (conversions = 16-19% and yields = 2-6%), although some selectivity (4:1 for 2-methoxystilbene) towards the formation of the distal isomer, i.e. methyl 3-(2-methoxyphenyl)-2-phenylpropanoate, was observed. Since the alkoxycarbonylation of alkynes is a well-documented reaction and these substrates could also function as starting material for the synthesis of isoflavonoids, albeit with an additional reduction step, the investigation was changed to the methoxycarbonylation of substituted diphenylacetylenes. In order to evaluate the influence of electron-donating and electron-withdrawing substituents on the rings of the phenylphenylacetylenes on the regioselectivity of the reactions, 4-methoxyphenyl- and (2-methoxyphenyl)phenylacetylene were prepared both in 69% yield by utilizing the Sonogashira coupling under conventional heating conditions (CuI/DABCO/K2CO3/DMF). (2,4-Dimethoxyphenyl)phenylacetylene was prepared in 91% yield by utilizing the Pd(PPh3)2Cl2/CuI/Et2NH/DMF reagent system under microwave irradiation (200 W). The electron-deficient diphenylacetylenes, (4- trifluoromethanesulfonyloxyphenyl)phenylacetylene, 4-methoxyphenyl-4'-trifluoromethanesulfonyloxyphenylacetylene and 4-methoxyphenyl-2',4'-bis(trifluoromethanesulfonyloxy)- phenylacetylene, were prepared in overall 81%, 87% and 19% yields via Sonogashira coupling and formation of the triflate from the free phenolic analogues. The 2-, 4-methoxy and 4-triflate substituted diphenylacetylenes, with the exception of (2,4- dimethoxyphenyl)phenylacetylene, were excellent substrates for the methoxycarbonylation reaction catalysed by Pd(OAc)2/Al(OTf)3/BINAP and gave good to excellent conversions (>97%) and yields (89%, 89% and 71%). Owing to Lewis acid catalysed methanol addition to the triple bond and subsequent demethylation, (2,4-dimethoxyphenyl)phenylacetylene gave only 35% of the desired product, which was accompanied by 46% of the corresponding deoxybenzoin. While some selectivity towards the proximal isomer of the esters were found for the two monomethoxy substituted diphenylacetylenes (2:1, proximal:distal), the methoxy carbonylation of (4-trifluoromethanesulfonyloxyphenyl)phenylacetylene gave the two esters in a ratio of 1:1. Methoxycarbonylation of the 4-methoxyphenyl-4'-trifluoromethanesulfonyloxyphenylacetylene and 4-methoxyphenyl-2',4'-bis(trifluoromethanesulfonyloxy)- phenylacetylene led to the two ester products in 71 and 72% yields, respectively with the proximal isomer (carboxylate function next to the methoxy carrying ring) obtained in a 3:1 and excellent 18:1 ratio, respectively. It was thus amply demonstrated that substituted diphenylacetylenes can be methoxycarbonylated successfully and that high selectivity towards the isomer that would allow cyclization to the 6-membered heterocyclic ring of the isoflavonoid nucleus is possible. Method development for the preparation of diphenylacetylenes with substitution patterns resembling those found in naturally occurring isoflavonoids and the synthesis of those isoflavonoids could therefore be embarked upon with confidence. Complete development of this new methodology towards the synthesis of isoflavonoids and the preparation of these compounds in enantiomerically pure form through stereoselective reduction of the remaining double bond in the methoxycarbonylated diphenylacetylenes, will receive further attention in a follow-up investigation.
Thesis (Ph.D. (Chemistry)--University of the Free State, 2018
Keywords: Alkenes; Alkynes; Palladium catalysed hydroesterification; Isoflavonoids; Methoxycarbonylation; Reactivity; Regioselectivity